Determinants of Tax Non-Compliance in Budget-Friendly Boutique and Economy-Class Hotels in Nepal - Ojha, Gaurav (Nepalese Journal of Hospitality and Tourism Management, 2026)
This study examines tax non-compliance behavior among budgetfriendly boutique and economy-class hotels in Nepal with reference to perceived fairness of the tax system, cost of tax compliance, coercive power of tax authorities, complexity of the tax system, and peer influence and social norms. A quantitative cross-sectional research design has been applied in this study to analyze the potential impact of these factors on the tax non-compliance behavior of these small, medium-sized, and economical hotels in Nepal. Data was collected from employees associated with 93 budget-friendly boutique and economyclass hotels located in Kathmandu, Lalitpur, Bhaktapur, Pokhara, and Bharatpur. Here, N=187 owner/investors, hotel managers, and heads of accounts and finance departments participated in this study. The results indicate that the cost of tax compliance and peer influence/social norms are influential determinants of tax non-compliance behavior among budget-friendly boutiques and economy-class hotels. Although counterintuitive, this study challenges the conventional deterrencebased assumption that coercive enforcement improves tax compliance behavior. This study concludes that tax regulators need to implement peer-based interventions and compliance-focused recognition programs and adopt supportive rather than punitive enforcement strategies for tax adherence among budget-friendly small- and medium-sized hotels in Nepal.